Desenvolva:
a) (x-a) elevado a 2.
Soluções para a tarefa
Respondido por
1
x^2-2xa+a^2
![{(x - a)}^{2} = (x - a) \times (x - a) = {x}^{2} - 2xa + {a}^{2} {(x - a)}^{2} = (x - a) \times (x - a) = {x}^{2} - 2xa + {a}^{2}](https://tex.z-dn.net/?f=+%7B%28x+-+a%29%7D%5E%7B2%7D+%3D+%28x+-+a%29+%5Ctimes+%28x+-+a%29+%3D+%7Bx%7D%5E%7B2%7D+-+2xa+%2B+%7Ba%7D%5E%7B2%7D+)
Perguntas interessantes
Matemática,
11 meses atrás
Ed. Física,
11 meses atrás
Ed. Física,
11 meses atrás
Geografia,
1 ano atrás
Português,
1 ano atrás